Maternal Obesity Increases Oxidative Stress in Placenta and It Is Associated With Intestinal Microbiota - Hu, Chengjun; Yan, Yingli; Ji, Fengjie; Zhou, Hanlin (Frontiers in Cellular and Infection Microbiology, 2021)
Maternal obesity induces placental dysfunction and intestinal microbial dysbiosis. However, the associations between intestinal microbiota and placenta dysfunction are still unclear. In the present study, a gilt model was used to investigate the role of maternal obesity on placental oxidative stress, mitochondrial function, and fecal microbiota composition, meanwhile identifying microbiota markers associated with placental oxidative stress. Twenty gilts were divided into two groups based on their backfat thickness on parturition day: namely Con group (average backfat thickness = 33 mm), and Obese group (average backfat thickness = 39 mm). The results showed that Obese group was lower than Con group in the birth weight of piglets. Compared with the Con group, the Obesity group exhibited an increased oxidative damage and inflammatory response in placenta, as evidenced by the increased concentrations of placental reactive oxygen species (ROS), protein carboxyl, and interleukin-6 (IL-6). Obesity group was lower than Con group in the concentrations of placental adenosine triphosphate, citrate synthase, and complex I activity. In addition, a lower propionate level and Bacteroidetes abundance in faeces was seen in the Obese Group. Furthermore, the concentrations of placental ROS, protein carboxyl, and IL-6 were positively correlated with the abundance of Christensenellaceae_R-7_group and negatively correlated with that of norank_f__Bacteroidales_S24-7_group. In conclusion, these findings suggest that maternal obesity might impair oxidative and inflammatory response in placenta through modulating intestinal microbiota composition.